Mesenteric Vascular Disease Current Therapy - Oderich, Gustavo S. (Springer New York : Imprint: Springer, 2015)
This book represents the first comprehensive textbook devoted to the standard of care, current guidelines and innovations in the field of mesenteric vascular disease. The book reviews imaging modalities, diagnostic work up, physiologic tests, traditional open surgical techniques and novel endovascular approaches. Technical aspects of both open surgical and endovascular techniques are provided by experts in the field, with illustrations and photographs of key steps for each type of procedure. Results of epidemiologic studies and national databases are summarized, as well as large institutional experiences. An evidence-based approach is used for recommendations regarding best therapies. Diagnostic approaches including imaging and novel physiologic tests, including gastric tonometry and oxygen light spectroscopy are also covered. Mesenteric Vascular Disease: Current Therapy will serve as a very useful resource for clinicians, surgeons, interventionalists, gastroenterologists and researchers dealing with and interested in mesenteric vascular diseases.